Effect of the passive recovery period on the lactate minimum speed in sprinters and endurance runners - Denadai, B. S.; Higino, W. P. (Sports Medicine Australia, 2004)
The objective of this study was to verify the effect of the passive recovery time following a supramaximal sprint exercise and the incremental exercise test on the lactate minimum speed (LMS). Thirteen sprinters and 12 endurance runners performed the following tests: 1) a maximal 500 m sprint followed by a passive recovery to determine the time to reach the peak blood lactate concentration; 2) after the maximal 500 m sprint, the athletes rested eight mins, and then performed 6 x 800 m incremental test, in order to determine the speed corresponding to the lower blood lactate concentration (LMS1) and; 3) identical procedures of the LMS1, differing only in the passive rest time, that was performed in accordance with the time to peak lactate (LMS2). The time (min) to reach the peak blood lactate concentration was significantly higher in the sprinters (12.76+/-2.83) than in the endurance runners (10.25+/-3.01). There was no significant difference between LMS1 and LMS2, for both endurance (285.7+/-19.9; 283.9+/-17.8 m/min; r= 0.96) and sprint runners (238.0+/-14.1; 239.4+/-13.9 m/min; r= 0.93), respectively. We can conclude that the LMS is not influenced by a passive recovery period longer than eight mins (adjusted according with the time to peak blood lactate), although blood lactate concentration may differ at this speed. The predominant type of training (aerobic or anaerobic) of the athletes does not seem to influence the phenomenon previously described.